Electrochemical aptasensor for analyzing alpha-fetoprotein using RGO–CS–Fc nanocomposites integrated with gold–platinum nanoparticles. Issue 41 (1st October 2020) - Li, Wenzhan; Chen, Min; Liang, Jintao; Lu, Chunting; Zhang, Min; Hu, Fangrong; Zhou, Zhide; Li, Guiyin
Abstract : Electrochemical aptasensor for analyzing AFP using RGO–CS–Fc nanocomposites integrated with gold–platinum nanoparticles and AFP aptamer has been developed. The AFP aptasensor showed satisfactory selectivity, reproducibility and stability. Abstract : Herein, a label-free electrochemical aptasensor for alpha-fetoprotein (AFP) analysis was established. The AFP aptamer (AFP-Apt), as the recognition molecule, was immobilized on the surface of a screen-printed carbon electrode, which was modified by gold–platinum metallic nanoparticles and reduced graphene oxide–chitosan–ferrocene nanohybrids (Au–Pt NPs/RGO–CS–Fc), to build the AFP electrochemical aptasensor. The construction process of the aptasensor was characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, and electrochemical impedance spectroscopy. With the addition of AFP, the formation of the AFP-aptamer conjugation blocked the electron transfer reaction, reducing the differential pulse voltammetric responses of the current of Fc in the RGO–CS–Fc nanohybrids. By optimizing the experimental parameters, AFP could be detected with the dynamic concentration range of 0.001 to 10.0 μg mL −1 and with a detection limit of 0.3013 ng mL −1 . In addition, the approach was manifested to have good selectivity, reproducibility, and stability. The fabricated aptasensor had a good recovery rate of 102.36% to 118.09% in real human serum samples. This work demonstrates that the electrochemical aptasensor is a useful tool for analyzing AFP inexpensively, rapidly, and accurately.